THE PROBLEM OF THE USE OF NEW ORAL ANTICOAGULANTS IN CANCER PATIENTS RECEIVING CHEMOTHERAPY - A. A. Rumyantsev; I. A. Pokataev; T. V. Kozlov; N. A. Rumyantsev (Столичная издательская компания, 2015)
Despite large number of known risk factors of venous thromboembolism (VTE) in cancer patients existing prediction models do not allow definite identification of cancer patients that have indications for anticoagulant prevention. Besides, heparin and warfarin use for VTE prevention in cancer is accompanied by some problems. New oral anticoagulants (NOAC) are promising drugs for use in oncology practice; however their use is complicated by the lack of data on efficacy and safety in these patients, potential drug interactions and the possibility of unpredictable changes in effect during chemotherapy. Widespread use of NOAC for the prevention and treatment of tumor-associated VTE prior to phase III trials is not recommended. However, the criteria for selection of patients for whom the study of the efficacy and safety of NOAC is a priority can now be developed.